Uma proposta de modelo de maturidade em gestão da sustentabilidade para o setor bancário - Inácio, Leticia da Silva (2020)
The pursuit of sustainable development has become ever larger, gaining ground in the business environment as well. The banking sector, despite having low direct social and environmental impact compared to other sectors of the economy, has a huge indirect impact, mainly due to the activities of its clients. Because of its role as an intermediary, it can influence the pace and direction of this development, both by collaborating with its customers' transition to a sustainable economy and by transforming their own business model and product offering. The level of commitment to sustainability can vary, so measuring sustainability performance and identifying its position at different maturity levels allows for the choice of more effective business decisions to seek results improvement. Despite this relevance, there are few studies on the measurement sustainability in the banking sector and there is no work that completely and comprehensively addresses the maturity of sustainability in this sector. In this context, this research aims to propose a model to classify the degree of maturity in sustainability management for the banking sector, resulting in an evolutionary framework of sustainability management based on three stages (reactive, preventive and strategic) encompassing seven sustainability competences (strategic management, integration into internal processes, organization, external relationships, environmental processes, social processes and economic processes). For this, a theoretical model was built from a systematic literature review and later applied to the case of the two largest Brazilian commercial banks. Thus, the present study brings both academic and practical contributions, also standing out for being comprehensive and one of the pioneers in Brazil.